Gene silencing pathway RNA-dependent RNA polymerase of Neurospora crassa: yeast expression and crystallization of selenomethionated QDE-1 protein. - Laurila, MR; Salgado, P; Makeyev, E; Nettelship, J; Stuart, D; Grimes, J; Bamford, D (2005)
The RNA-dependent RNA polymerase, QDE-1, is a component of the RNA silencing pathway in Neurospora crassa. The enzymatically active carboxy-terminal fragment QDE-1 DeltaN has been expressed in Saccharomyces cerevisiae in the presence and absence of selenomethionine (SeMet). The level of SeMet incorporation was estimated by mass spectrometry to be approximately 98%. Both native and SeMet proteins were crystallized in space group P2(1) with unit cell parameters a=101.2, b=122.5, c=114.4A, beta=108.9 degrees , and 2 molecules per asymmetric unit. The native and SeMet crystals diffract to 2.3 and 3.2A, respectively, the latter are suitable for MAD structure determination.